Far-field pressure measurements of elliptic jets discharged close to a wing - Ramos Proenca, Anderson; Lawrence, Jack L. T. (IOP Publishing, 2022)
This paper presents a preliminary experimental investigation into the acoustics of two elliptical jet nozzles installed close to a wing model. Acoustic pressure data is obtained for a range of observer polar angles mounted in the far field of the jets. Three nominal jet Mach numbers, namely 0.4, 0.6 and 0.8 are studied. Results suggest that the elliptic jets surveyed provide a noise reduction of the jet-surface installation noise source. The noise reduction is maximum in the forward arc and in the order of 1 dB for the fully-corrected overall sound pressure level data. Additionally, the noise benefit exists only when the minor axis of the elliptical nozzle is mounted parallel to the wing trailing edge. It is hypothesised that the reduction in the jet plume cross-section width limits the scattering of the near pressure field by the wing trailing edge to a lower frequency range. The jet mixing noise source, however, is seen to increase with decreasing nozzle exit-plane aspect ratio. The three jet velocities surveyed suggest the consistency of the key results discussed in the paper. Investigation of the jet turbulent flow structures and jet near pressure field is under way.